Adverse drug reactions monitoring among breast cancer patients in a tertiary care teaching hospital - Anisha, S.; Nandha, S. Rajendra; Suseela, Supriya Selvakumar (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Breast cancer is responsible for 13% of deaths among women globally. The present study aimed to assess adverse drug reactions (ADRs) in breast cancer patients receiving treatment in a tertiary care teaching hospital. Methods: This retrospective and descriptive study was conducted in the oncology department at sree mookambika institute of medical sciences, Kulasekharam, covering six months from May 2022 to November 2022. The study includes patients of any age diagnosed with breast cancer, treated with chemotherapy, and who developed at least one ADR during or after treatment. Patients who developed ADRs due to fresh blood or blood product infusion and had a history of drug abuse or accidental poisoning were excluded from the study. Results: Three hundred fifty-eight breast cancer patients were evaluated, of which 142 developed ADRs. The study revealed that breast cancer was most prevalent among women aged 41-50. Seven (4.92%) had a history of tobacco smoking, 129 (90.85%) patients were married, and only 13 (9.15%) were unmarried. The most commonly prescribed chemotherapeutic drug for breast cancer patients was docetaxel (19.01%), Cyclophosphamide (15.49%) and nab. paclitaxel (12.67%). The study found that the most frequent ADR observed among the patients was febrile neutropenia (18.30%), followed by nausea and vomiting 14.79%). Causality assessment reported that 61.27% (87) of the ADRs were probable, and 29.58% (42) were possible. Conclusions: Spontaneous adverse drug reporting and structured management are essential for monitoring the safe use of drugs. The findings suggest the need for effective pharmacovigilance programs and improved patient care in administering chemotherapeutic agents.